The Koreans who they are, what they want, where their future lies - Breen, Michael (Thomas Dunne Books, 2004)
"Although Korea has only recently found itself a part of the global stage, it is a country with a rich and complex past. Early history shows that Koreans had a huge influence on ancient Japan, and their historic achievements include being the first culture to use metal movable type for printing books. However, much of their history is less positive: it is marred with political violence, poverty, and war - aspects that would sooner be forgotten by the Koreans, who are trying to focus on their promising future." "In The Koreans, Michael Breen provides an in-depth portrait of the country and its people. An early overview of the nature and values of the Korean people provides the background for a more detailed examination of the complex history of the country, in particular its division into the Communist north and pro-Western south."--BOOK JACKET.